THE IMPORTANCE OF ENGLISH LANGUAGE LEARNING IN MODERN EDUCATION - Tokhirov Samandar Khusniddin ugli (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation: This thesis examines the importance of learning English in modern education and its growing role in global communication. The study highlights the significance of English in academic achievement, professional development, and access to information. It discusses the major benefits of English language proficiency, including improved communication skills, better career opportunities, and enhanced cognitive abilities. The thesis also analyzes common challenges faced by learners, such as grammatical difficulties, pronunciation issues, and lack of practice. Furthermore, it presents effective strategies for successful language learning, including regular practice, vocabulary development, and the use of modern technologies. The findings demonstrate that English language proficiency is an essential skill in the twenty-first century and contributes significantly to personal, educational, and professional success.